Evaluation of the Regional Public Service Agency Budget Absorption Level in Gresik, East Java - Wahyuni, Eni; Ellina, Agusta Dian (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Absorption of the expenditure budget is one of the performance assessments that is still a challenge in the Regional Public Service Agency (BLUD) of Health Center in Gresik Regency. The purpose of this study is to explore the evaluation of the level of absorption of the budget of the regional public service agency of the Health Center in Gresik Regency.Subjects and Method: This qualitative study was conducted in Health Center in Gresik Regency in 2 to 28 october 2022. The informants in this study were the owner or person in charge of the clinic with a total of 24 (twenty-four) people with triangulation of sources. The qualitative data and information were analyzed using source triangulation.Results: In the Resource Indicator which includes knowledge, attitudes and workload at the BLUD Health Center, it is known that the informant's knowledge regarding budgeting and BLUD absorption is quite sufficient. In addition, with the change in the status of the Health Center to BLUD, the workload of health workers has also increased. All informants have a good attitude and commitment in implementing BLUD Health Center. The unavailability of regulations related to HR management, accounts payable, investment management and cooperation management in the context of financial independence at the BLUD Health Center in Gresik Regency. There has never been any monitoring assistance from the planning process to the absorption of the BLUD budget at the Gresik Regency Health Center by the Gresik Regency Regional Financial Revenue Management Agency (BPPKAD).Conclusion: It is necessary to immediately issue regulations in the form of Decrees and Regent's Regulations related to the management of Human Resources, accounts payable, investment management, and the management of cooperation with the BLUD Health Center in Gresik Regency.Keywords: Budget, BLUD & Public Health CenterCorrespondence: Eni Wahyuni. Masters Program in Public Health, Strada Indonesian Institute of Health Sciences. Jl. Manila, No. 37, Sumberece, Kediri, East Java 64133, Indonesia. Email: eniwahyuni@gmail.com. Mobile: +6282233337053.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.03